Ethnomathematics in the Traditional inheritance Distribution System of the Sasak Tribe In Sade Village - Ulya Widya Arsyanita; Diniarti; Muh. Jibril Madhani (Tinta Emas Institute, 2025)
The division of inheritance in the customary law system, particularly in Sade Village, reflects the application of mathematical concepts in the division process. This article aims to reveal the existence of provisions based on mathematical calculations that can be analyzed using mathematical concepts. This research uses a qualitative research type with an ethnographic approach, employing data collection techniques through observation, interviews, and documentation. Through the processes of data reduction, data presentation, and conclusion drawing, it was found that inheritance distribution in the local community involves mathematical principles, such as rational numbers, social arithmetic operations, and the application of linear equation systems (LES). This research shows that although conducted traditionally, the inheritance distribution in Sade Village has indirectly adopted mathematical patterns relevant to the social and cultural practices of the local community.